Application of Lean Analysis Value Stream Mapping to Minimize Waste: ACase Study of CV Jeans Gallery, Indonesia - Yasin, Ruchbandi Rahmat T.; Junus, Stella; Simatupang, Rudolf (Industrial and Domestic Waste Management, 2025)
CV Jeans Gallery is a convection company that faced significant challenges related to waste in its production process, including high waiting times, workload imbalances, and inefficiencies in production flow. The primary aim of this study was to identify and reduce waste through the application of the Value Stream Mapping (VSM) method. VSM was employed to map the production process, identify non-value-added activities, and uncover opportunities for improvement to enhance overall efficiency. Data was collected through direct observation, interviews with employees, and recording the time taken for various production processes. The analysis revealed that several types of waste occurred across the production stages. This included inventory waste, characterized by excessive raw material stock, and waiting waste, particularly during the design of embroidery patterns, where delays were frequently observed. Additionally, defects were identified as another significant form of waste, occurring when products could not be used by customers due to quality issues.